2022
DOI: 10.1039/d1fo03852d
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic effect of fructans from Agave salmiana on probiotic lactic acid bacteria and in children as a supplement for malnutrition

Abstract: An imbalanced gut microbiota predisposes the development of nutritional disorders and chronic gastrointestinal diseases. Several studies have shown improvements on the host’s health by enhancing the microbiota with prebiotics that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, a higher amount of agave inulin and FOS were released after a 3 h catalyzed reaction for all agave leaf fractions especially in the bottom fraction compared to the 18 h enzymatic hydrolysis. Huazano-García and López evaluated the activity of endo- and exo- inulinase from Aspergillus niger , and the mix of both inulinases on agave inulin from A. angustifolia stem. The authors reported an increase of FOS (DP4, DP7, and DP8, mostly) after 48 h of the endo- inulinase reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a higher amount of agave inulin and FOS were released after a 3 h catalyzed reaction for all agave leaf fractions especially in the bottom fraction compared to the 18 h enzymatic hydrolysis. Huazano-García and López evaluated the activity of endo- and exo- inulinase from Aspergillus niger , and the mix of both inulinases on agave inulin from A. angustifolia stem. The authors reported an increase of FOS (DP4, DP7, and DP8, mostly) after 48 h of the endo- inulinase reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Different approaches have been developed in order to obtain short chain FOS. Nevertheless, they all include either the use of previously extracted agave inulin or the juice from the A. tequilana pine . On the contrary, our work searches to obtain FOS by using the whole A. salmiana leaf, which, indeed, is an important source of fructans and a species that has not been used for such purpose.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary interventions with fructans have become one of the main strategies to modulate the composition and function of the gut microbiota ( Carbonero, 2021 ; Vandeputte et al, 2017 ; Hiel et al, 2019 ). Several studies have demonstrated that fructans sourced from Cichorium intybus ( Vandeputte et al, 2017 ; Reimer et al, 2020 ), Agave tequilana ( Márquez-Aguirre et al, 2013 ; Padilla-Camberos et al, 2018 ; Sáyago-Ayerdi et al, 2021 ), Agave salmiana ( Castillo Andrade et al, 2019 ; Daniel et al, 2022 ; Martinez-Martin et al, 2022 ), Codonopsis pilosula ( Fu et al, 2018 ), Asparagus cochinchinensis ( Sun et al, 2020 ), and Polygonatum cyrtonema ( Zhang et al, 2021 ), selectively stimulate the growth of beneficial bacteria such as Prevotella , Megamonas and Bifidobacterium , improving health with human colon ( Sun et al, 2020 ) (Table 2). For instance, a diet supplemented with Agave species fructans in an animal model stimulated the growth of Bifidobacterium and Lactobacillus and inhibited growth of Clostridium in the large intestine ( Castillo Andrade et al, 2018 , 2019 ; Castillo Andrade et al, 2021 ; Martínez et al, 2022 ).…”
Section: Fructans Application By Humanmentioning
confidence: 99%
“…Clinical trials also show that consumption of inulin-rich vegetables or snack bars increase the ratio of Bifidobacterium and help reduce the dietary fiber gap prevalent in modern life ( Hiel et al, 2019 ; Teferra, 2021 ; Reimer et al, 2020 ). In a double-blind trial in which Agave salmiana fructans were added to children's diets, it has been demonstrated that those children who supplemented with fructans had a more considerable weight gain, an increased number of lactic acid bacteria, and a decreased concentration of volatile organic compounds ( Daniel et al, 2022 ). Furthermore, interventions that add fructans from Agave salmiana to probiotic yogurt have been reported to increase the abundance of intestinal microbiota and stimulate the growth of beneficial bacteria in overweight or obese children ( Martinez-Martin et al, 2022 ).…”
Section: Fructans Application By Humanmentioning
confidence: 99%
“…The prebiotic used can either directly support the efficacy of the probiotic itself or it can support the resident microbiota. For example, fructans can be very supportive of probiotic lactic acid bacteria and stimulate their growth ( 69 ), and glucose derived oligosaccharides like polydextrose can increase intestinal Ruminococcus intestinalis and enhance butyrate production ( 70 ). These are just a few of many in an exhaustive list that is beyond the scope of this review.…”
Section: Introductionmentioning
confidence: 99%